UNDERSTANDING THE EFL LECTURERS' BELIEFS ABOUT THEIR PROFESSIONAL LEARNING FROM THE LENS OF MALCOLM KNOWLES THEORY OF ANDRAGOGY - Purwanti, Eko (Journal of Foreign Language Teaching and Learning, 2017)
The establishment of Teacher and Lecturer Law No. 14/ 2005 has an implication that all lecturers in Indonesia should maintain their professionalism in order to improve the teaching and learning process.In an attempt to be professional, lecturers are expected to carry out on-going professional learning. This study aims to seek the perceptions of English as a Foreign Language lecturers about their professionallearning in a language training centre of a private university in Indonesia. Underpinned by interpretive paradigm and naturalistic design, the study employed qualitative methods using focus group interviews by which seven EFL lecturers were included as the participants. The finding of the study reveals that professional learning activities conducted by the participants are perceived as a compulsory activity, a result of their experiences, their learning orientation, their learning passion, and their internal motivation.These findings, in fact, corroborate the principles of adult learning theory of Malcolm Knowles called Andragogy which is based on the learning principles such as self-concept, readiness to learn, orientation to learning, adult learner experience, and motivation to learn.